SOCIAL MEDIA USAGE AND TEXTISM AMONG UNDERGRADUATE STUDENTS AT RIVERS STATE UNIVERSITY, PORT HARCOURT - Geoffrey, Jaja, Irene (PT. Antis International Publisher, 2025)
Objective: The use of social media by youths is appearing to continue to soar in recent times globally. This study investigated social media usage and textism among undergraduate students of Rivers State University, Port Harcourt, guided by the research questions: in what ways do the undergraduate students at Rivers State University, Port Harcourt utilize social media, and why do they use textism in their daily interaction on social media. Method: The study adopted a descriptive survey design and proportionate sampling techniques. Data were obtained from primary and secondary sources such as questionnaires, journals, and textbooks. The uses and gratifications theory was applied to analyze how undergraduate students at Rivers State University use social media in their everyday lives. Result: Findings revealed that undergraduate students at Rivers State University, Port Harcourt utilize web-based media platforms to communicate with family and friends, to upload and download pictures and videos, and that students use textism in their daily interactions on social media because it makes communication easier, simpler, and faster. Novelty: The study recommends that undergraduate students at Rivers State University, Port Harcourt should use social media more for academic purposes and moderate the time spent on social networking sites and the use of textism to reduce the risks of addiction.